Family income, perfectionism and social anxiety among higher education students - Mohd Noor, Norhayati; Abu Talib, Mansor (Universiti Sultan Azlan Shah, 2019)
University students are members of the youth community who have enormous potential to contribute towards the development of the country. The health and wellbeing of students are reflected in their low social anxiety and perfectionism. Family SES factors such as income also affect social fears and aviodance and influence the adaptive and maladaptive perfectionism among university students. This study, conducted using the survey method was performed on 1618 university students aged 18 – 25 year across Malaysia selected via a multistage stratified sampling as respondents. A self administered questionaire containing demographic information and the Almost Perfect Scale- Revised (Slaney, Rice, Mobley, Trippi, & Ashby, 2001), and Liebowitz Social Anxiety Scale (Heimberg et al.,1999), to tap on perfectionism, and social anxiety was used for data collection. Results of this study found that slightly more than half of the respondents scored higher than the mid-point of perfectionism standard, indicating high level of perfectionism standard (M = 36.55, SD = 6.31). However, slightly more than half of the respondents scored lower than the mid-point of the remaining study variables, suggesting low levels of perfectionism discrepancy (M = 56.36, SD = 10.81), fear social anxiety (M = 28.36, SD = 12.70), and avoidance social anxiety (M = 26.00, SD = 12.36). As for social anxiety, majority have moderate fear and avoidance while 5.6% have severe fear and 3.8% reported severe avoidance social anxiety. The results show that majority of students in Institutions of Higher Learning (IHL) have positive social outlook and low maladaptive perfectionism personalities even though the family SES is at a moderate level. The implications of the study findings on family roles are also discussed in this article.